Photocatalytic Properties of Mixed-Crystalline Titanate Nanotubes Prepared by Hydrothermal Reaction - Wang, Yanli; Wang, Jia; Wu, Qiuxia; Tan, Shun; Guo, Huijiao; Wu, Minghong; Jiao, Zheng (Asian Journal of Chemistry, 2011)
In this paper, mixed-crystalline titanate nanotubes (TiO2-NTs) are grown by hydrothermal reaction in a 10M NaOH aqueous solution for the application in photocatalysis. The morphology and structure of prepared samples are characterized by XRD, SEM, TEM and BET. TiO2-NTs have uniform shapes. XRD analysis indicates that the mainly phase are anatase TiO2 and rutile TiO2. The photocatalytic properties of TiO2-NTs were investigated. It is found that the TiO2-NTs with mixed crystal structures exhibited improved photocatalytic activity in comparison with rutile TiO2 nanoparticle and the commercial Degussa P-25. The photocatalytic mechanism of TiO2- NTs was also discussed.